2017
DOI: 10.1007/s13197-016-2450-2
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and sensory characteristics of steviolbioside synthesized from stevioside and its application in fruit drinks and food

Abstract: Steviolbioside (Sb) was synthesized from stevioside and characterized by infrared, nuclear magnetic resonance ( 1 H NMR and 13 C NMR) spectroscopy. The purity melting point, solubility, acute toxicity, heat stability and sensory properties of Sb were evaluated. Physicochemical and sensory properties of low calorie fruit drinks and shortened cake prepared by replacing sugar with Sb were evaluated. Sb was stable in neutral or acidic aqueous solutions maintained at 100°C for 2 h. The sweetness intensity rate of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Increasing the ratio of glycyrrhizin more than 25% negatively affected the sensorial properties of tested cakes. These data are agreement with Khattab et al (2017) who found that there was no significant differences between the organoleptic properties of cakes prepared using sugar and those prepared replacing sugar with 50% steviolbioside.…”
Section: Physicochemical and Organoleptic Properties Of Cake Containisupporting
confidence: 92%
See 1 more Smart Citation
“…Increasing the ratio of glycyrrhizin more than 25% negatively affected the sensorial properties of tested cakes. These data are agreement with Khattab et al (2017) who found that there was no significant differences between the organoleptic properties of cakes prepared using sugar and those prepared replacing sugar with 50% steviolbioside.…”
Section: Physicochemical and Organoleptic Properties Of Cake Containisupporting
confidence: 92%
“…Hardness and total work cycle values decreased in cake containing glycyrrhizin compared with the control. Where Khattab et al (2017) found that the cake made with 100% steviolbioside as a sugar replacer had the lower values of hardness, hardness work cycle and total work cycle values than in case of the sample with sucrose. No differences were shown in deformation of hardness among all treatments compared with the control samples.…”
Section: Physicochemical and Organoleptic Properties Of Cake Containimentioning
confidence: 99%
“…Additionally, according to the previous literature, inulin should be used in high amounts comparing to the other texturizing carbohydrates in order to exert desired effects (Aidoo et al, 2017; Azevedo et al, 2016); therefore, it was used 0-6% w/w. Moreover, previous studies have revealed that replacing sugar with stevia, in the fruit nectar samples, will reduce the Brix (Khattab et al, 2017;Saniah et al, 2012), while in the current study the Brix loss, resulted by replacing sugar with stevia, was well controlled by inulin addition.…”
Section: The Impact Of Inulin and Stevia On Brixsupporting
confidence: 53%
“…Due to the direct effect of sweeteners on flavor, determining desirable sensory characteristics, using appropriate concentration of stevia was very significant. Replacing sucrose with stevia seems to cause a bitter aftertaste and an adverse effect on the flavor at high concentrations that this bitterness could be attributed to the presence of rebaudioside A in stevia powder (Khattab et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…After taste is caused by the presence of compounds that are still left in the mouth and affects the nerve response. The sweetness of stevia cause of steviolbioside [16,17]. Bitterness and astringency of black tea felt in the mouth are influenced by polyphenol compounds, caffeine compounds and proteins [18].…”
Section: Fig3 Sensory Test Of Sucrose Stevia Leaves Black Tea Andmentioning
confidence: 99%